Assessment of economic competencies using a matrix puzzle and a document analysis. Issue 4 (2nd October 2018) - Walstad, William B.
Abstract: In this article, the author presents two alternative approaches to the assessment of competencies in economics. The first is a concept assessment as a matrix puzzle. The rows of the matrix are the economic changes and the columns are the economic outcomes. To solve the puzzle, students state which change is associated with an outcome and which is not. The second one is a performance assessment as a document analysis that gives students documents and asks them to use them to analyze a realistic economic problem. Students use higher-order thinking in the process of selecting information from the document and in preparing their written answers. The explanation of each assessment type uses tasks related to supply and demand as examples.